IKLIM KOMUNIKASI ORGANISASI DAN MOTIVASI KERJA PIMPINAN DALAM MEWUJUDKAN MISI PERUSAHAAN - Satria Kusuma (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
The  objectives  of  this  research  are  to  observe  and  analyze  climate  organizational  communication  and  leadership motivation  performance  in  achieving  corporate  mission  of  PLN  Inc.  Surakarta.  The  method  used  for  this  research  is descriptive  qualitative.  The  analysis  proves  that  the  communication  climate  in  PLN  Inc  is  supporting  the  leadership motivation performance. Several supporting factors of the finding are trust, support, honesty, and transparency among the  leaders  of  the  top,  middle  and  lower  level.  Humans  are  motivated  by  communication  climate  and  creative  and participative  working  system,  when  someone  has  sense  of  belonging,  automatically,  they  will  support  the  process  of achieving the corporate mission. A satisfying communication climate can be achieved through creating a shared vision to assure the free flow of information and allow subordinates to participate in decision making processes. Meanwhile, the  existing  organizational  climate  is  formed  through  several  factors;  responsibility,  organizational  or  management structure  which  is  tailored  based  on  the  needs  of  companies,  and  working  motivation  from  the  leaders  so  that  every problem can be solved through solid teamwork to achieve the corporate mission. Keywords: organizational communication, communication climate, working motivation